Metastatic follicular carcinoma of thyroid in maxilla - Kumar, Caliaperoumal Santhosh (Medknow Publications & Media Pvt Ltd, 2013)
Metastasis to the oral region is very rare and accounts for less than 1% of oral malignant tumors. Breast, lung, kidney, adrenal, gastro intestinal tract and prostates are most common primary tumors from which metastasis to oral region occur frequently. Metastasis from thyroid gland is extremely rare to oral region. We present an unusual case of metastatic follicular carcinoma of thyroid in maxilla. The significance of this report is that the secondary lesion was the only symptom of the primary tumor and helped us in diagnosis and treatment of disease.